Lithuania : Banking System Assessment - World Bank (Washington, DC, 2013)
The Bank of Lithuania (BoL), the Central Bank, was established in 1990. BoL has the exclusive right to grant and revoke licenses to local and foreign banks and to supervise their activities. Private commercial banking boomed from 1991 to 1994 while bank regulation was lax. In late 1995, a bank crisis caused failures of most of the Lithuanian banks, and the remaining banks resulted in better managed and supervised institutions. BoL also applied tougher regulation on the banking sector. All commercial banks now need to have their financial records audited every year by an international auditing firm. This report includes the following headings: risks and contingency crisis management in the Lithuanian banking system; credit risk and regulatory issues; and description of corporate debt restructuring procedures in Lithuania.